Cytoskeletal dynamics in parasites - Reber, Simone B.; Singer, Mirko; Frischknecht, Friedrich (Current opinion in cell biology, 2024)
Cytoskeletal dynamics are essential for cellular homeostasis and development for both metazoans and protozoans. The function of cytoskeletal elements in protozoans can diverge from that of metazoan cells, with microtubules being more stable and actin filaments being more dynamic. This is particularly striking in protozoan parasites that evolved to enter metazoan cells. Here, we review recent progress towards understanding cytoskeletal dynamics in protozoan parasites, with a focus on divergent properties compared to classic model organisms.